A MARKET PENETRATION FRAMEWORK FOR HYPERSCALE DATA CENTERS IN INDONESIA: A MIXED-METHODS STUDY - Fariz Pradana; Harimukti Wandebori (RADJA PUBLIKA, 2026)
This study develops a market penetration framework for a global hyperscale data center operator that faces slow customer acquisition in Indonesia despite having strong infrastructure capabilities and financial backing. A sequential exploratory mixed-methods design was employed, comprising semi-structured interviews with eight industry experts and a structured survey of 40 decision-makers from hyperscaler, financial services, enterprise, and government segments. The findings reveal four distinct customer clusters, AI Pioneers (hyperscalers), Regulated Guardians (financial services), Pragmatic Operators (enterprises), and Sovereign Stewards (government), each with unique needs regarding AI-readiness, compliance, managed services, and data sovereignty. A critical trust deficit (92% perceive limited local track record) and low brand awareness (52.5% unaware) are identified as primary barriers. Importance-Performance Analysis indicates that ARSA GDC has potential competitive advantages in liquid cooling readiness, high-density infrastructure, and sustainability, which directly address key incumbent weaknesses. The resulting five-layer framework prioritizes securing a hyperscaler anchor tenant as the critical catalyst, supported by asset-based value propositions, strategic partnerships, operational excellence, and a phased implementation roadmap. The framework provides actionable guidance for new entrants in capital-intensive B2B markets.